Isothermal amplification of long DNA fragments at low temperature by improved strand displacement amplification - Yinhua Zhang; Ashley N Luck; Nathan A Tanner (BioTechniques)
Strand displacement amplification (SDA) is an isothermal amplification technique wherein amplification of a nucleic acid is initiated by nicking enzyme activity at sites flanking the target. Diagnostic SDA is very fast but requires precise optimization and is limited to very short amplicons. Here we report an enhanced approach by addition of single-stranded DNA binding protein, crowding agents and dUTP to enable amplification of kilobase-length products at low temperatures. Additionally, we pair this improved SDA with a novel carryover contamination prevention, eliminating amplifiable DNA at the end of the reaction to reduce contamination risk. Taken together these developments increase the utility and versatility of SDA, broadening the reach of this powerful but uncommonly used method.